An audit of cord blood sampling at a large city hospital. (16th November 2010) - Hall, S
Abstract : Introduction: Analysis of paired cord blood samples remains the gold standard assessment of uteroplacental function and provides an objective measure of fetal response to labour. The Royal College of Obstetricians and Gynaecologists state that a normal result largely excludes intrapartum hypoxia as a cause of brain damage1 and therefore, in the instance of a diagnosis of cerebral palsy, a normal sample is essential to defend against litigation. At Sunderland Royal Hospital (SRH) cord blood samples are taken for high-risk deliveries, according to the indications stated in Trust Guidelines. Aim: To determine whether cord samples are taken when indicated, and whether results are documented on labour records. Methods: A retrospective audit of the first 100 deliveries at SRH in December 2008. Data were collected from the labour ward register, fetal blood sampling record and medical notes. Information collected included: any indications for cord sampling, whether a sample was taken, if the sample was paired and whether it was documented. Results: 47 deliveries had an indication for cord sampling, however only 38 (81%) of these had a sample taken. Samples were least likely to be taken when the indication was intrauterine growth restriction. 95% of samples taken were paired. 52% were correctly documented. Conclusion: Many cord samples for high-risk deliveries are not being taken, despite being indicated. Therefore, for these cases any future claims for cerebral palsy would be indefensible. Furthermore, as many diagnoses of cerebral palsy also follow low-risk deliveries, the author recommend that paired cord samples should be taken for all deliveries. This recommendation was subsequently adopted by SRH.